Two new species of the genus Plumaroides Brothers, 1974 (Hymenoptera: Chrysidoidea, Plumariidae) from Argentina - Diez, Patricia A.; Fidalgo, Patricio (Zootaxa, 2012)
Two new species of the genus Plumaroides Brothers, 1974 from Catamarca and La Rioja provinces of Argentina P. aquilusDiez & Fidalgo, sp. nov. and P. tapilophus Diez & Fidalgo, sp. nov. are described and illustrated. A key to separate males of five known species of Plumaroides is provided.